2020
DOI: 10.1007/s00436-019-06576-4
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in canine dirofilariosis in Austria—do we face a pre-endemic status?

Abstract: A retrospective study based on cases of canine dirofilariosis presented to the University of Veterinary Medicine, Vienna or diagnosed by private practitioners throughout Austria, from 1998 to 2018 was conducted to investigate the long-term development and current state of canine dirofilarial infections in Austria. Included in this study were 146 dogs which were tested positive for D. immitis and/or D. repens. The most commonly used diagnostic methods and the probable geographical origins of the infections were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 52 publications
(65 reference statements)
0
19
1
1
Order By: Relevance
“…We did not detect any D. immitis infection in dogs sampled in 2019, although D. immitis is believed to follow D. repens in its expansion in Central and NE Europe 2 , 10 , 16 , 17 , 34 . However, D. immitis infections in sled dogs participating in training and races should be easily noticed by owners due to exercise intolerance, a characteristic consequence of heartworm infection 50 .…”
Section: Discussioncontrasting
confidence: 55%
“…We did not detect any D. immitis infection in dogs sampled in 2019, although D. immitis is believed to follow D. repens in its expansion in Central and NE Europe 2 , 10 , 16 , 17 , 34 . However, D. immitis infections in sled dogs participating in training and races should be easily noticed by owners due to exercise intolerance, a characteristic consequence of heartworm infection 50 .…”
Section: Discussioncontrasting
confidence: 55%
“…A recent study on canine dirofilariosis conducted in Austria revealed that the number of dogs infected with D. repens and D. immitis has increased since 2014, reaching a peak in 2018 [ 41 ]. The infected animals had mostly been imported as shelter or stray dogs by animal welfare organizations or had an international travel history, both facilitated by the Pet Travel Scheme (Regulation [EU] No.…”
Section: Discussionmentioning
confidence: 99%
“…576/2013 of the European Parliament and of the Council as of 2013). In the majority of cases, the infected dogs were relocated from or had traveled to regions known to be endemic for Dirofilaria spp., such as Hungary, Greece, Croatia, Serbia, Slovenia, Spain, Romania and Slovakia [ 25 , 41 47 ]. Dogs are the main reservoir hosts for Dirofilaria spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canine heartworm disease has been considered endemic in Hungary since 2007; since then, the number of cases has increased dramatically [49]. Sonnberger et al (2020) show that just by importing dogs from Hungary to Austria, the number of positive tested dogs in Austria increased by a factor of 20-30 over the last ten years [50]. The fi rst records on autochthonous D. repens infections in Austrian dogs were published in 2009, near the border of Hungary and Slovakia; confi rmation of an endemic status was achieved by the detection of skinworm DNA in mosquitos a few years later [51,52].…”
Section: Canine and Feline Dirofi Lariosismentioning
confidence: 99%